Analisis Beban Kerja Petugas Rekam Medis Bagian Filing dengan Metode WISN di RSD Mangusada Badung Tahun 2020 - Raisa Putri Ramadhani; Sustin Farlinda; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Workload analysis is an attempt to find out the time used by officers to complete a particular task which is expected to know the proportion of the number of officers needed in a particular work unit in an agency. The Importance of Workload Analysis must be carried out routinely in order to obtain information about the description of the workload of units in an agency. This research aims to analyze the workload of medical records officers so that the workload level of the officer is known using the WISN (workload indicator staff need) method, The type of this research is qualitati with data collection techniques in the form of observation, interviews, documentation, and library research. The subjects of this study were 9 staff officers which 1 head of filing affair and 8 implementing staff. Based on human resource qualification research, there was enough job description, but based on patient visit rates after RME implementation since early 2020 showed a drastic decrease in visits where before the RME was applied the average number of patient visits 20,000 patients per month, while after applying RME for January and February there were 6,485 and 6,116. The results of the calculation of the workload know that the number of officers needed is the ideal number of officers needed, which is 4.96 so that it is rounded up to 5 so that it can be concluded that there is a need for relocation of as many as 4 people to other work units so that Mangusada Regional Hospital can provide maximum human resources as efficiently as possible.